Evaluation of Risk Factors Associated with Diabetic Foot Ulcers in Saudi Arabia - Al-Ayed, Mousab Y.; Ababneh, Mutasem; Robert, Asirvatham Alwin; Salman, Ahmed; Al Saeed, Abdulghani; Al Dawish, Mohamed Abdulaziz (Current Diabetes Reviews, 2019)
Background and Aims: Considering that diabetic foot ulceration is one of the major health issues globally, we aimed to evaluate the risk factors associated with foot ulcers in patients with type 2 diabetes mellitus (T2DM). Methods: A total of 81 T2DM patients (age range: 40-80 years) registered at the Diabetes Treatment Center, Prince Sultan Military Medical City (PSMMC), Riyadh, Saudi Arabia between April and September 2015 were included in this cross-sectional study after purposive selection and assigning of patient numbers. The selected participants were interviewed and examined, and their medical records were reviewed for sensory, vibratory, and painful neuropathies; vascular insufficiency; retinopathy; and dermatological variations. The Wagner’s classification system was employed to evaluate the stage of patients’ foot ulcers. Results: Among the study participants [mean age range: 56.4 ± 6.72 years; 53 males (65.4%)], cases of loss of protective sensation, foot deformity, amputation history, and dermatological abnormalities were notable. The Wagner gradation value of ulcers were grade 0 for 16% study population, grade 1 for 35.8%, grade 2 for 45.7%, grade 3 for 2.5%, and grades 4 and 5 for 0%. Approximately 19% of the patients had a previous case of amputation and 29.6% had nail disease. The most common footwear reported to be used by the patients was sandals shoes (46%). Conclusion: The issues of loss of protective sensation, vascular insufficiency, deformity, previous amputations, and dermatological abnormalities of the lower limbs were found to be most common among the foot ulceration patients. The study findings thus recommend regular foot examination, following basic hygiene habits, encouragement of the use of appropriate footwear, patient education about foot ulcers, and prompt treatment for minor injuries to prevent further ulceration in DM patients.
Keywords: Saudi Arabia